Emerging Severe and Fatal Infections Due to Klebsiella pneumoniae in Two University Hospitals in France - Decré, Dominique (American Society for Microbiology, 2011)
Severe infections caused by hypermucoviscous Klebsiella pneumoniae have been reported in Southeast Asian countries over the past several decades. This report shows their emergence in France, with 12 cases observed during a 2-year period in two university hospitals. Two clones (sequence type 86 [ST86] and ST380) of serotype K2 caused five rapidly fatal bacteremia cases, three of which were associated with pneumonia, whereas seven liver abscess cases were caused by K1 strains of ST23.